2001
DOI: 10.1093/emboj/20.22.6550
|View full text |Cite
|
Sign up to set email alerts
|

Non-homologous end-joining proteins are required for Agrobacterium T-DNA integration

Abstract: Agrobacterium tumefaciens causes crown gall disease in dicotyledonous plants by introducing a segment of DNA (T‐DNA), derived from its tumour‐inducing (Ti) plasmid, into plant cells at infection sites. Besides these natural hosts, Agrobacterium can deliver the T‐DNA also to monocotyledonous plants, yeasts and fungi. The T‐DNA integrates randomly into one of the chromosomes of the eukaryotic host by an unknown process. Here, we have used the yeast Saccharomyces cerevisiae as a T‐DNA recipient to demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 56 publications
2
98
1
1
Order By: Relevance
“…Indeed, if the link between genetic instability and integration continues to be reinforced, one could use illegitimate integration sites as telltale indicators of unstable loci in the genome. Finally, while some experiments have investigated the genetic components necessary for efficient illegitimate integration in some systems, 100,104,105 detailed knowledge about the mammalian cellular factors necessary for these processes is also lacking. A better understanding of the mechanisms and factors governing illegitimate DNA integration would allow for better control of these events and, ultimately, an improved and safer use of DNAmediated genome modification in laboratory and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if the link between genetic instability and integration continues to be reinforced, one could use illegitimate integration sites as telltale indicators of unstable loci in the genome. Finally, while some experiments have investigated the genetic components necessary for efficient illegitimate integration in some systems, 100,104,105 detailed knowledge about the mammalian cellular factors necessary for these processes is also lacking. A better understanding of the mechanisms and factors governing illegitimate DNA integration would allow for better control of these events and, ultimately, an improved and safer use of DNAmediated genome modification in laboratory and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…NHEJ and HR (BRCA1) proteins were also shown to have an effect on integration frequencies in other systems: NHEJ deficiency was shown to inhibit integration in yeast, and BRCA1 À/À cells had a 5-to 10-fold reduction in retroviral DNA integration. 104,105 Other types of repair machinery might influence integration as well. For example, a deficiency of mismatch repair proteins (known to be involved in the disruption and correction of mismatched heteroduplex DNA that can arise during NHEJ and HR DNA repair) can increase the frequency of illegitimate integration 15-fold.…”
Section: Proposed Mechanisms Of Illegitimate Dna Integrationmentioning
confidence: 99%
“…The process of T-DNA integration is not well understood. Studies in yeast have identified yeast genes required for T-DNA integration both via nonhomologous recombination and homologous recombination (van Attikum et al, 2001(van Attikum et al, , 2003. Several Arabidopsis thaliana ecotypes and mutants deficient in T-DNA integration have also been identified and characterized (Nam et al, 1997(Nam et al, , 1998Mysore et al, 2000aMysore et al, , 2000bAnand et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Illegitimate integration resembles nonhomologous end-joining (NHEJ) repair, because it is enhanced by DNA damage, especially double-strand breaks (DSBs); it is homology-independent and involves end joining (12)(13)(14). In addition, there are several reports of reduced integration of retroviral DNA and Arabidopsis T elements in NHEJ-defective cells (15)(16)(17)(18). However, it is also clear that NHEJ proteins are not essential for illegitimate integration, because many reports describe reasonable levels of integration in cells lacking NHEJ proteins (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%